Social media adoption as a full mediator between entrepreneurial orientation and MSME performance - Marisa Intan Prawesti; Yessy Artanti; Sanaji Sanaji (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to examine the effect of entrepreneurial orientation on MSME performance with social media adoption as a mediating variable. The research was conducted on MSMEs in the food, beverage, and fashion sectors located in seven sub-districts of Sidoarjo Regency, East Java, Indonesia. A quantitative approach was employed using a survey method with 130 respondents selected through purposive sampling. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) with SmartPLS 3. The findings reveal that entrepreneurial orientation does not directly affect MSME performance but has a significant positive effect on social media adoption. Social media adoption, in turn, positively and significantly influences MSME performance. Furthermore, social media adoption fully mediates the relationship between entrepreneurial orientation and MSME performance. These results suggest that entrepreneurial orientation needs to be channeled through social media adoption to improve performance outcomes. Keywords: Entrepreneurial Orientation; Social Media Adoption; MSME Performance; Dynamic Capability Theory; Diffusion of Innovation Theory